Contributions of Neuropsychology to the Study of Ancient Literature - Fabbro, Franco; Fabbro, Anastasia; Crescentini, Cristiano (Frontiers in Psychology, 2018)
The present work introduces the neuropsychological paradigm as a new approach to studying ancient literature. In the first part of the article, an epistemological framework for the proper use of neuropsychology in relation to ancient literature is presented. The article then discusses neuropsychological methods of studying different human experiences and dimensions already addressed by ancient literatures. The experiences of human encounters with gods among ancient cultures are first considered, through the contributions of Julian Jaynes and Eric R. Dodds. The concepts of right and left in the Bible, and that of soul are then discussed. Ecstatic experience in Paul of Tarsus is also presented, with a particular focus on glossolalia. Neuroscientific differences between mindful and unitive meditative practices are then described referring to ancient Buddhist literature, and finally a brief description of dreams in ancient Greek literature is proposed. Neuropsychology variously enables a more profound understanding of themes characterizing human experiences that ancient literature has already explored; these investigations prove that the collaboration of neuroscience and humanistic studies can return fruitful and interesting results.